On the importance of the primer activation signal for initiation of tRNA(lys3)-primed reverse transcription of the HIV-1 RNA genome - Huthoff, Hendrik (Oxford University Press, 2003)
Initiation of reverse transcription is a complex and regulated process in all retroviruses. Several base pairing interactions have been proposed to occur between the HIV-1 RNA genome and the specific tRNA(lys3) primer. The tRNA primer can form up to 21 bp with the primer binding site (PBS), and an additional 8 bp interaction may form between the primer activation signal (PAS) in the HIV-1 RNA and sequences within the TΨC arm of the tRNA. The latter interaction is further analyzed in this in vitro study with mutant RNA transcripts that were designed to preclude the PAS interaction. These mutant transcripts are able to efficiently bind the tRNA primer, but they exhibit a profound defect at initiating reverse transcription. This defect is specific for the tRNA primer because it is not observed for PBS-bound DNA oligonucleotide primers. These results reinforce the model of regulated reverse transcription in which the PAS-mediated interaction is critical for efficient initiation.